Patient-Specific Cell Communication Networks Associate With Disease Progression in Cancer - Gibbs, David L.; Aguilar, Boris; Thorsson, Vésteinn; Ratushny, Alexander V.; Shmulevich, Ilya (Frontiers in Genetics, 2021)
The maintenance and function of tissues in health and disease depends on cell-cell communication. This work shows how high-level features, representing cell-cell communication, can be defined and used to associate certain signaling 'axes' with clinical outcomes. We generated a scaffold of cell-cell interactions and defined a probabilistic method for creating per-patient weighted graphs based on gene expression and cell deconvolution results. With this method, we generated over 9,000 graphs for TCGA patient samples, each representing likely channels of intercellular communication in the tumor microenvironment. It was shown that cell-cell edges were strongly associated with disease severity and progression, in terms of survival time and tumor stage. Within individual tumor types, there are predominant cell types, and the collection of associated edges were found to be predictive of clinical phenotypes. Additionally, genes associated with differentially weighted edges were enriched in Gene Ontology terms associated with tissue structure and immune response. Code, data, and notebooks are provided to enable the application of this method to any expression dataset ( https://github.com/IlyaLab/Pan-Cancer-Cell-Cell-Comm-Net).